Preparation method and use method of potassium-based porous geopolymer soil acidity modifier
By preparing potassium-based porous geopolymer soil acid conditioner and combining geopolymer with solid waste to form a porous structure, the problems of nutrient loss and heavy metal fixation in acidic soil are solved, and efficient and environmentally friendly soil improvement and solid waste utilization are achieved.
Patent Information
- Application Number
- CN202510938582.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-08
- Publication Date
- 2025-10-14
AI Technical Summary
Acidic soils have high aluminum and iron oxide content, low base saturation and serious nutrient loss. Traditional improvement methods are costly and ineffective, and are unable to supplement mineral nutrients such as K+ and Ca2+, and have limited heavy metal fixation capacity.
The preparation method of potassium-based porous geopolymer soil acid conditioner is adopted, which combines geopolymer materials with solid waste and forms a porous structure through alkali-induced reaction. As a soil conditioner and fertilizer, it has high alkalinity, long-term effect and heavy metal fixation ability.
It can continuously neutralize soil acidity, stabilize heavy metals, and improve soil base saturation and compressive strength over a long period of time, thus solving the shortcomings of traditional amendments and achieving environmentally friendly and sustainable soil improvement and solid waste utilization.
Smart Images

Figure CN120775593A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soil improvement, and in particular relates to a preparation method and a use method of a potassium-based porous geopolymer soil acidity improver. Background Art
[0002] Acidic soil (pH < 7) is widely distributed in tropical and subtropical regions. Its high aluminum and iron oxide content, low base saturation, and nutrient loss seriously restrict agricultural production, leading to crop yield reduction, heavy metal activation (such as aluminum toxicity), and ecological degradation. In addition, since acidic soil weathers more thoroughly and clay minerals are mainly 1:1 kaolinite, the cation exchange capacity is low and the adsorption capacity for cations is weak. Under humid conditions, the soil undergoes strong leaching, resulting in K + , Ca 2+ Mg 2+ A large amount of leaching of mineral nutrients such as K + Although traditional improvement methods such as applying lime or gypsum can neutralize acidity in the short term, they are costly, unsustainable, and prone to soil compaction and inability to replenish K. + , Ca 2+ Therefore, it is urgent to develop a fertilizer that is environmentally friendly, long-lasting, and resource-recyclable, and can be used as a fertilizer to supplement K + , Ca 2+ New and improved technology for mineral nutrients such as nutrient.
[0003] Geopolymers are inorganic polymers formed through an alkali-induced reaction using a siliceous-aluminous matrix (such as metakaolin and fly ash). Their unique chemical structure imparts high strength, acid and alkali resistance, heavy metal binding capacity, and environmental friendliness. Currently, geopolymers are primarily used as building materials, and no technology has been published for their use in improving acidic soils. Summary of the Invention
[0004] To address the shortcomings of the prior art, the present invention provides a method for preparing and using a potassium-based porous geopolymer soil acidity improver. This invention utilizes geopolymers to achieve an innovative "waste-to-waste" approach, providing a synergistic solution for acidic soil improvement and solid waste resource utilization.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing a potassium-based porous geopolymer soil acid conditioner comprises the following steps:
[0007] Step 1: Stirring and dispersing an activator, a main ingredient, and water to form a geopolymer slurry; the weight ratio of the activator, the main ingredient, and the water is 10-120:10-100:10-100; the main ingredient is composed of a powder with activating activity and solid waste, and the weight ratio of the powder with activating activity to the solid waste is 1:0-9;
[0008] Step 2: mixing a foaming agent and water in a weight ratio of 1:5-200, dispersing the mixture into prefabricated foam, and then adding the prefabricated foam into the geopolymer slurry prepared in step 1 and mixing the mixture evenly to obtain a modifier slurry, wherein the weight proportion of the foaming agent in the geopolymer slurry is 0%-70%;
[0009] Step 3: pouring the modifier slurry prepared in step 2 into a mold and curing it in an oven;
[0010] Step 4: After the improver slurry is solidified, it is taken out of the mold, ground and sieved to obtain the potassium-based porous geopolymer soil acid improver.
[0011] Furthermore, the activator in step 1 includes sodium hydroxide, potassium hydroxide, potassium silicate, sodium silicate, potassium carbonate, sodium carbonate, and calcium sulfate; any one of them or any combination of two or more can be selected when used.
[0012] Furthermore, the powder with excitation activity described in step 1 includes metakaolin, volcanic ash, fly ash, slag, silica fume, artificial silica alumina gel, waste glass powder, rice husk ash, and synthetic powder; any one of these or any combination of two or more can be selected when used. The slag described in the present invention is granulated blast furnace slag.
[0013] Furthermore, the solid waste in step 1 includes red mud, manganese slag, steel slag, copper slag, lead slag, zinc slag, tailings, waste rock, desulfurization gypsum, concrete fragments, brick and tile fragments, and wood waste; when used, any one of them or any combination of two or more can be selected.
[0014] Furthermore, the types of foaming agents described in step 2 include hydrogen peroxide, aluminum powder, plant protein foaming agent, animal protein foaming agent, azodicarbonamide, fatty alcohol polyoxyethylene ether AEO-9, sodium lauryl sulfate K12, sodium rosin acid, citric acid, and baking soda; when used, you can choose any one of them or any combination of two or more.
[0015] Furthermore, the dispersion speed in step 1 is 100-5000 r / min, and the dispersion time is 1-10 min; the dispersion speed in step 2 is 500-2500 r / min, and the dispersion time is 1-10 min.
[0016] Furthermore, in step 3, the curing temperature of the oven is 20-150° C., and the curing time is 1 min-96 h.
[0017] Furthermore, in step 4, the mesh aperture range is between 0.1 μm and 1 cm.
[0018] Furthermore, the potassium-based porous geopolymer soil acid conditioner has a compressive strength of 0-120 MPa and a bulk density of 0.1-3.0 g / cm 3 .
[0019] The present invention also provides a method for using the potassium-based porous geopolymer soil acidity improver, comprising the following steps: spreading the potassium-based porous geopolymer soil acidity improver as a soil improver and fertilizer into acidic soil; for slightly acidified soil with a pH of 5.5-6.0, the spreading amount of the potassium-based porous geopolymer soil acidity improver is 0.5-1 ton / hectare; for moderately acidified soil with a pH of 5.0-5.5, the spreading amount of the potassium-based porous geopolymer soil acidity improver is 1-2 tons / hectare; for severely acidified soil with a pH <5.0, the spreading amount of the potassium-based porous geopolymer soil acidity improver is equal to or greater than 2-5 tons / hectare.
[0020] The present invention also provides the application of the potassium-based porous geopolymer soil acidity improver in engineering soil remediation, wherein the engineering soil remediation includes roadbed reinforcement and slope stabilization, and the remediation construction method includes the following steps: firstly, the original soil is crushed and sun-dried, then the potassium-based porous geopolymer soil acidity improver is evenly spread, and finally, the above steps are layered, mixed, and compacted, and the operation is repeated three times in total, with the compacted thickness of each layer not less than 10 cm, and then covered with film and maintained for 24 hours; every 1m 3 20% by weight of the potassium-based porous geopolymer soil acid conditioner was added to the original soil (dry weight 1.5 t).
[0021] The present invention has the following beneficial effects:
[0022] 1) Traditional acidic soil improvement methods such as lime improvement, although lime can quickly neutralize soil acidity, its effect duration is short, and it is easy to cause calcium ion leaching due to rainfall or irrigation, causing the soil pH value to drop again (reacidification). And after lime improvement, the base ions (such as potassium, calcium, magnesium) in the soil are easily leached, resulting in a decrease in soil fertility. The potassium-based porous geopolymer soil acid conditioner of the present invention has high alkalinity (pH 9-12), can continuously neutralize soil acidity for a long time, and avoid the problem of reacidification after traditional lime improvement. At the same time, the three-dimensional network structure of the improver of the present invention can continuously release nutrients such as potassium and calcium, which can effectively improve soil base saturation and improve soil physical and chemical properties.
[0023] 2) Traditional chemical amendments only inhibit heavy metal activity by adjusting pH, but fail to completely immobilize them, requiring additional bioremediation measures. However, the three-dimensional network structure of the potassium-based porous geopolymer soil acidifier of the present invention stabilizes heavy metals (such as lead and cadmium) in the soil through adsorption or chemical bonding, reducing their bioavailability. For example, the cured steel slag geopolymer soil acidifier can achieve a lead immobilization rate of over 90%.
[0024] 3) Traditional acidic soil improvement methods, such as organic fertilizer or green manure, mainly improve soil fertility and have limited effect on strengthening soil structure. The potassium-based porous geopolymer soil acidity improver of the present invention improves soil compressive strength (up to 1.5 times that of ordinary cement soil) and shear resistance significantly better than traditional lime soil or pure clay, making it suitable for engineering soil remediation (such as roadbed reinforcement and slope stabilization). For example, the original roadbed soil is acidic, highly plastic red clay, and its bearing capacity will drop sharply by 30% during the rainy season. After improvement, traditional cement soil still has freeze-thaw cracking and insufficient shear resistance. The use of the potassium-based porous geopolymer soil acidity improver of the present invention can improve soil compressive strength and effectively repair engineered soil.
[0025] 4) From the perspective of environmental benefits and sustainable development, traditional acidic soil improvement, such as lime improvement, requires high-temperature calcination of calcium carbonate for production, resulting in high carbon emissions, and landfill or simple composting may cause groundwater pollution or methane emissions. The preparation process of the potassium-based porous geopolymer soil acidic improver of the present invention does not require high-temperature calcination (traditional cement production requires above 1400°C), reducing energy consumption by 70% and carbon emissions by 60%. Secondly, the curing process of the potassium-based porous geopolymer soil acidic improver of the present invention stabilizes harmful components in solid waste (such as alkaline substances in red mud) through chemical bonding, avoiding heavy metal leakage or dust pollution caused by traditional landfilling. Moreover, the improver of the present invention has both soil improvement and solid waste utilization functions. For example, its high alkalinity can neutralize acidic soil and solidify heavy metals in solid waste at the same time. Traditional technology requires step-by-step implementation (such as applying lime first and then planting green manure), which is less efficient. In addition, the present invention uses industrial solid wastes such as red mud, steel slag, and fly ash as geopolymer raw materials, which can not only reduce material costs but also solve the problem of solid waste accumulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical picture of the potassium-based porous geopolymer soil acid conditioner obtained in Examples 1-12 of the present invention, wherein A, B, C, D, E, F, G, H, I, J, K, and L correspond to Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, Example 8, Example 9, Example 10, Example 11, and Example 12, respectively;
[0027] Figure 2 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 1;
[0028] Figure 3 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 2;
[0029] Figure 4 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 3;
[0030] Figure 5 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 4;
[0031] Figure 6 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 5;
[0032] Figure 7 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 6;
[0033] Figure 8 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 7;
[0034] Figure 9 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 8;
[0035] Figure 10 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 9;
[0036] Figure 11 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 10;
[0037] Figure 12 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 11;
[0038] Figure 13 Graphs showing the 1-, 3-, and 7-day compressive strength and bulk density of the potassium-based porous geopolymer soil acid conditioner obtained in Example 12;
[0039] Figure 14These are optical images of the potassium-based porous geopolymer soil acid conditioner obtained in Example 2, Example 3, Example 4, Example 5, Example 6, and Example 12, wherein A, B, C, D, E, and F correspond to Example 2, Example 3, Example 4, Example 5, Example 6, and Example 12, respectively;
[0040] Figure 15 The pH change patterns over time when limestone, the potassium-based porous geopolymer soil acid conditioner obtained in Examples 1-4, and Example 12 are mixed with acidic soil respectively. DETAILED DESCRIPTION
[0041] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments and drawings. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0042] Example 1
[0043] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0044] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 24 hours;
[0045] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0046] The actual picture of the pure slag-based polymer soil acidity improver with potassium silicate water glass as the activator obtained in Example 1 is as follows: Figure 1 As shown in A.
[0047] The compressive strength and bulk density of the soil acid conditioner obtained in Example 1 were tested. The compressive strength and bulk density of the obtained 1, 3 and 7 days are shown in the figure. Figure 2 .like Figure 2 As can be seen, the soil acid conditioner prepared in Example 1 exhibited high strength on the first day and continued to increase steadily thereafter, while the bulk density remained essentially stable after three days. This indicates that the free water in the geopolymer had been largely removed by three days. The conditioner of this example exhibited high strength, was not easily crushed, and maintained a loose soil state for a long time, facilitating root penetration and water infiltration.
[0048] Example 2
[0049] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0050] (2) Weigh 0.3 g of AB-FP1 plant protein foaming agent (triterpenoid saponins extracted from the fruit of the Chinese honey locust tree) and 30 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 r / min for 3 min to obtain prefabricated foam;
[0051] (3) 11.5 g (5% of the total slurry) of the prefabricated foam obtained in step (2) was added to the slurry obtained in step (1) and manually stirred for 3 minutes until the slurry was uniform;
[0052] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 12 hours;
[0053] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0054] The actual picture of the slag-based porous geopolymer soil acidity improver obtained in Example 2 with potassium silicate water glass as the activator and 5% vegetable protein foam added is as follows: Figure 1 As shown in B; the optical image of the soil acid conditioner obtained in Test Example 2 is as shown in Figure 14 As shown in A in the figure, the holes formed are relatively uniform.
[0055] The 1-, 3- and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 2 are as follows: Figure 3 As shown, the soil acidic conditioner prepared in Example 2 remained substantially stable on the third day, with a slight decrease in bulk density in the first three days and substantially stable after three days, indicating that the free water in the geopolymer had been substantially removed three days prior. The low-density conditioner of this embodiment is itself loose and porous, and after application, it can increase the soil aggregate structure, improve air permeability and water permeability, and break the common compaction problem of acidic soils (acidification can destroy aggregates, leading to soil hardening). In addition, the conditioner of this embodiment has high strength and is not easily crushed, and can maintain a loose soil state for a long time, which is beneficial for root penetration and water infiltration.
[0056] Example 3
[0057] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0058] (2) Weigh 0.3 g of plant AB-FP1 protein foaming agent and 30 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 r / min for 3 min to obtain prefabricated foam;
[0059] (3) Add 23 g of the prefabricated foam obtained in step (2) (accounting for 10% of the total slurry) to the slurry obtained in step (1) and stir manually for 3 minutes until the slurry is uniform;
[0060] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 12 hours;
[0061] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0062] The actual picture of the slag-based porous geopolymer soil acidity improver obtained in Example 3 with potassium silicate water glass as the activator and 10% vegetable protein foam added is as follows: Figure 1 As shown in C; the optical image of the soil acid conditioner obtained in Test Example 3 is as shown in Figure 14 As shown in B in the figure, the holes formed are relatively uniform.
[0063] The 1-, 3-, and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Example 3 were tested. Figure 4 As shown, the soil acid conditioner prepared in Example 3 remained basically stable on the third day, with a slight decrease in bulk density in the first three days and then basically stable after three days. The conditioner of this example also has the characteristics of low density and high strength.
[0064] Example 4
[0065] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0066] (2) Weigh 0.5 g of AB-FP1 plant protein foaming agent and 50 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 r / min for 3 min to obtain prefabricated foam;
[0067] (3) 34.5 g (15% of the total slurry) of the prefabricated foam obtained in step (2) was added to the slurry obtained in step (1) and manually stirred for 3 minutes until the slurry was uniform;
[0068] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 12 hours;
[0069] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0070] The actual picture of the slag-based porous geopolymer soil acidity improver obtained in Example 4 with potassium silicate water glass as the activator and 15% vegetable protein foam added is as follows: Figure 1 As shown in D; the optical image of the soil acid conditioner obtained in Test Example 4 is as shown in Figure 14 As shown in C in the figure, the formed holes are relatively uniform.
[0071] The 1-, 3- and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 4 are as follows: Figure 5 As shown, the soil acid conditioner prepared in Example 4 remained basically stable on the third day, with a slight decrease in bulk density in the first three days and then basically stable after three days. The conditioner of this example also has the characteristics of low density and high strength.
[0072] Example 5
[0073] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0074] (2) Weigh 0.5 g of K12 foaming agent and 50 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 rpm for 3 min to obtain prefabricated foam;
[0075] (3) Add 23 g of the prefabricated foam obtained in step (2) (accounting for 10% of the total slurry) to the slurry obtained in step (1) and stir manually for 3 minutes until the slurry is uniform;
[0076] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 72 hours;
[0077] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0078] The actual picture of the slag-based porous geopolymer soil acidity improver obtained in Example 5 with potassium silicate water glass as the activator and 10% K12 foam added is as follows: Figure 1 As shown in E; the optical image of the soil acid conditioner obtained in Test Example 5 is as shown in Figure 14 As shown in D in the figure, the formed holes are relatively uniform.
[0079] The 1-, 3- and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 5 are as follows: Figure 6 As shown, the soil acid conditioner prepared in Example 5 remained basically stable on the third day, with a slight decrease in bulk density in the first three days and then basically stable after three days. The conditioner of this example also has the characteristics of low density and high strength.
[0080] Example 6
[0081] (1) Weigh 100 g of slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0082] (2) Weigh 0.3 g of sodium rosinate and 30 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 rpm for 3 min to obtain prefabricated foam;
[0083] (3) Add 23 g of the prefabricated foam obtained in step (2) (accounting for 10% of the total slurry) to the slurry obtained in step (1) and stir manually for 3 minutes until the slurry is uniform;
[0084] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 72 hours;
[0085] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0086] The actual picture of the slag-based porous geopolymer soil acidity improver obtained in Example 6 with potassium silicate water glass as the activator and 10% sodium rosinate foam added is as follows: Figure 1 As shown in F; the optical image of the soil acid conditioner obtained in Test Example 6 is as shown in Figure 14 As shown in Figure E, the formed holes are relatively uniform.
[0087] The 1-, 3- and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 6 are as follows: Figure 7 As shown, the soil acid conditioner prepared in Example 6 remained basically stable on the third day, with a slight decrease in bulk density in the first three days and then basically stable after three days. The conditioner of this example also has the characteristics of low density and high strength.
[0088] Example 7
[0089] (1) Weigh 100 g of metakaolin, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0090] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 96 hours;
[0091] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0092] The actual picture of the pure metakaolin-based polymer soil acidity improver with potassium silicate water glass as the activator obtained in Example 7 is as follows Figure 1 G shown in Example 1; Test Example 1 obtained with potassium silicate water glass as an activator of pure metakaolin-based polymer 1, 3, 7 days compressive strength and bulk density as shown Figure 8 As shown, the soil acid conditioner prepared in Example 7 has a high strength on the first day, and the strength increases rapidly thereafter and remains stable on the third day. The bulk density is also basically stable after three days, which indicates that the free water in the geopolymer is basically removed three days ago.
[0093] Example 8
[0094] (1) Weigh 100 g of metakaolin, 120 g of 1.0 M sodium silicate water glass, and 40 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min.
[0095] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 96 hours;
[0096] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0097] The physical picture of the pure metakaolin-based polymer soil acid conditioner with sodium silicate water glass as the activator obtained in Example 8 is as follows: Figure 1 The 1-, 3-, and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 8 are shown in FIG. Figure 9 As shown, the soil acid conditioner prepared in Example 8 has a high strength on the first day, and the strength increases rapidly thereafter and remains stable on the third day. The bulk density decreases slightly in the first three days and is basically stable after three days.
[0098] Example 9
[0099] (1) Weigh 100 g of metakaolin, 60 g of 1.0 M sodium silicate water glass, 60 g of 1.0 M potassium silicate water glass, and 25 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min;
[0100] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 96 hours;
[0101] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0102] The actual picture of the pure metakaolin-based polymer soil acid conditioner with sodium silicate / potassium water glass as the activator obtained in Example 9 is as follows: Figure 1 1, 3, 7 days compressive strength and bulk density of the soil acid conditioner obtained in Test Example 9 are shown in FIG. Figure 10As shown, the soil acid conditioner prepared in Example 9 has a relatively high strength on the first day, and then the strength increases evenly. The bulk density decreases slightly in the first three days and is basically stable after three days.
[0103] Example 10
[0104] (1) Weigh 20 g of slag, 80 g of red mud, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min;
[0105] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 24 hours;
[0106] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0107] The actual picture of the slag-red mud-based polymer soil acid conditioner with potassium silicate water glass as the activator obtained in Example 10 is as follows: Figure 1 The 1-, 3-, and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 10 are shown in FIG. Figure 11 As shown, the strength of the soil acid conditioner prepared in Example 10 was basically stable on the third day, and the bulk density decreased slightly in the first three days and was basically stable after three days.
[0108] Example 11
[0109] (1) Weigh 20 g of slag, 80 g of manganese slag, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min;
[0110] (2) Pour the prepared slurry into a mold and cure in an oven at 40°C for 24 hours;
[0111] (3) After removing the mold, the mold is removed, ground and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0112] The actual picture of the slag-manganese slag-based polymer soil acidity improver with potassium silicate water glass as the activator obtained in Example 11 is as follows: Figure 1 The 1-, 3-, and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 11 are shown in FIG. Figure 12 As shown in the figures, the slag-manganese slag-based polymer soil acidity improver prepared in Example 11 with potassium silicate water glass as the activator has higher strength than the slag-red mud-based polymer soil acidity improver prepared in Example 10 with potassium silicate water glass as the activator, and is basically stable on the third day. The bulk density decreases slightly in the first three days and is basically stable after three days.
[0113] Example 12
[0114] (1) Weigh 50 g of slag, 50 g of red mud, 120 g of 1.0 M potassium silicate water glass, and 10 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 2000 rpm for 5 min;
[0115] (2) Weigh 0.3 g of AB-FP1 plant protein foaming agent and 30 g of water, place them in a 500 ml plastic beaker, and disperse them in a disperser at 1000 r / min for 3 min to obtain prefabricated foam;
[0116] (3) Add 23 g of the prefabricated foam obtained in step (2) (accounting for 10% of the total slurry) to the slurry obtained in step (1) and stir manually for 3 minutes until the slurry is uniform;
[0117] (4) Finally, pour the prepared slurry into the mold and cure in an oven at 40°C for 24 hours;
[0118] (5) After removing the mold, the mold is removed, ground, and passed through a 1 mm sieve to obtain a potassium-based porous geopolymer soil acid conditioner.
[0119] The actual picture of the slag-red mud-based porous geopolymer soil acid conditioner obtained in Example 12 with potassium silicate water glass as the activator and 10% vegetable protein foam added is as follows: Figure 1 As shown in L; the optical image of the soil acid conditioner obtained in Test Example 12 is as follows Figure 14 As shown in F, the holes formed are symmetrical.
[0120] The 1-, 3- and 7-day compressive strength and bulk density of the soil acid conditioner obtained in Test Example 12 are as follows: Figure 13 As shown, the soil acid conditioner prepared in Example 12 showed a uniform increase in strength, a slight decrease in bulk density in the first three days, and a substantial stabilization after three days, indicating that the free water in the geopolymer had been substantially removed by three days. The conditioner of this example also exhibited low density and high strength.
[0121] Acidic soil, limestone, and the potassium-based porous geopolymer soil acid conditioner obtained in Examples 1-4 and 14 were crushed and passed through a 1 mm sieve. The mixture was then uniformly mixed with the acidic soil at a weight ratio of 1:2. The pH value of the acidic soil was determined in strict accordance with the National Environmental Protection Standard of the People's Republic of China (HJ 962-2018). The test results are as follows: Figure 15 As shown. Figure 15It can be concluded that after adding the soil acidity improver of each embodiment, the acidity of the soil is greatly improved, and the improvement effect is more obvious as the foaming increases; and the improvement of soil acidity is basically completed before 12 hours, and the subsequent pH change is not obvious; the pH change pattern of soil acidity improvement after adding limestone is similar to that of Example 3, but the pH shows a phenomenon of acidification after 1 month, while the pH of the acidic soil improved by the soil acidity improver of the embodiment of the present invention still maintains a stable upward trend after 1 month. The amount of foaming added in Example 3 is the same as that in Example 12, but the effect of improving acidic soil by adding solid waste is better.
[0122] Table 1 shows the variation of the leaching concentration of K ions of the potassium-based porous geopolymer soil acid conditioner obtained in Examples 2, 3, 4, and 7 over time.
[0123] Table 1
[0124]
[0125] The experiment uses inductively coupled plasma emission spectrometry (DB63 / T 1820-2020) to measure the K ion leaching concentration at different times. From the data in Table 1, it can be seen that as time goes by, a large amount of K ions are gradually leached in Examples 2, 3, 4, and 7, and the K ion concentration gradually increases with the increase in the amount of foaming agent and the increase in time. This is because the more foaming amount, the more pores there are, and the larger the contact area with the outside world. At the same time, it can be seen from the data in Table 1 that after 1 month of testing, each group of soil acid conditioner can continuously and slowly release K ions, proving that it can effectively improve soil base saturation and improve soil physical and chemical properties in the long term.
[0126] Table 2 shows the variation of the leaching concentration of Ca ions of the potassium-based porous geopolymer soil acid conditioner obtained in Examples 2, 3, 4, and 7 over time.
[0127] Table 2
[0128]
[0129] The experiment uses inductively coupled plasma emission spectrometry (DB63 / T 1820-2020) to measure the Ca ion leaching concentration at different times. From the data in Table 2, it can be seen that as time goes by, a large amount of Ca ions are gradually leached in Examples 2, 3, and 4, while there is almost no Ca ion leaching in Example 7. This is because the matrix of Examples 2, 3, and 4 is slag, while the matrix of Example 7 is metakaolin. It can be seen that slag is more suitable for preparing the soil acid conditioner of the present invention relative to metakaolin. At the same time, it can be seen from the data in Table 2 that after 1 month of testing, the soil acid conditioner of Examples 2-4 can continuously and slowly release Ca ions, proving that it can effectively improve soil base saturation and improve soil physical and chemical properties in the long term.
[0130] Table 3 shows the harmful ion leaching concentrations of Fe, Pb, Mn, Cu, Ni, Zn, and Sr of the potassium-based porous geopolymer soil acid conditioner obtained in Examples 10, 11, and 12.
[0131] Table 3
[0132]
[0133] According to China's current "Soil Environmental Quality Agricultural Land Soil Pollution Risk Control Standard (Trial)" (GB
[0134] 15618-2018), for Class II acidic soil with pH <6.5, the pollution limit of lead in soil is 250 mg / kg; the pollution limit of nickel in soil is 40 mg / kg; the pollution limit of copper in soil is 50 mg / kg; the pollution limit of zinc in soil is 200 mg / kg; according to the "Soil Environmental Quality Standard" (GB15618-1995), the pollution limit of iron in soil is 1000 mg / kg; the pollution limit of manganese in soil is 1000 mg / kg; the country has not yet clearly defined the limit for strontium, but the background value of strontium in Chinese soil is generally in the range of 50-300 mg / kg. As can be seen from the data in Table 3, the leaching of harmful ions in Examples 10, 11, and 12 all meet the above standards.
[0135] Although the present invention has been disclosed above with reference to preferred embodiments, this is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the definition of the claims.
Claims
1. A method for preparing a potassium-based porous geopolymer soil acid conditioner, characterized in that: The steps include: Step 1: Stirring and dispersing an activator, a main ingredient, and water to form a geopolymer slurry; the weight ratio of the activator, the main ingredient, and the water is 10-120:10-100:10-100; the main ingredient is composed of a powder with activating activity and solid waste, and the weight ratio of the powder with activating activity to the solid waste is 1:0-9; Step 2: mixing a foaming agent and water in a weight ratio of 1:5-200 and dispersing the mixture into a prefabricated foam, adding the prefabricated foam into the geopolymer slurry prepared in step 1 and mixing the mixture evenly to obtain a modifier slurry, wherein the weight proportion of the foaming agent in the geopolymer slurry is 0%-70%; Step 3: pouring the modifier slurry prepared in step 2 into a mold and curing it in an oven; Step 4: After the improver slurry is solidified, it is taken out of the mold, ground and sieved to obtain the potassium-based porous geopolymer soil acid improver.
2. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: The activator in step 1 includes sodium hydroxide, potassium hydroxide, potassium silicate, sodium silicate, potassium carbonate, sodium carbonate, and calcium sulfate.
3. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: The powder with excitation activity in step 1 includes metakaolin, volcanic ash, fly ash, slag, silica fume, artificial silica-alumina gel, waste glass powder, rice husk ash, and synthetic powder.
4. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: The solid wastes in step 1 include red mud, manganese slag, steel slag, copper slag, lead slag, zinc slag, tailings, waste rock, desulfurized gypsum, concrete fragments, brick and tile fragments, and wood waste.
5. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: The types of foaming agents described in step 2 include hydrogen peroxide, aluminum powder, plant protein foaming agent, animal protein foaming agent, azodicarbonamide, fatty alcohol polyoxyethylene ether AEO-9, sodium lauryl sulfate K12, sodium rosin acid, citric acid, and baking soda.
6. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: In step 3, the curing temperature of the oven is 20-150°C, and the curing time is 1 min-96 h.
7. The method for preparing a potassium-based porous geopolymer soil acidity conditioner according to claim 1, characterized in that: The sieve aperture in step 4 ranges from 0.1 μm to 1 cm.
8. The potassium-based porous geopolymer soil acid conditioner prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The potassium-based porous geopolymer soil acid conditioner has a compressive strength of 0-120 MPa and a bulk density of 0.1-3.0 g / cm 3 .
9. The method for using the potassium-based porous geopolymer soil acid conditioner according to claim 8, characterized in that: The method comprises the following steps: spreading the potassium-based porous geopolymer soil acid conditioner as a soil conditioner and fertilizer into acidic soil; for slightly acidified soil with a pH of 5.5-6.0, the spreading amount of the potassium-based porous geopolymer soil acid conditioner is 0.5-1 ton / hectare; for moderately acidified soil with a pH of 5.0-5.5, the spreading amount of the potassium-based porous geopolymer soil acid conditioner is 1-2 tons / hectare; for severely acidified soil with a pH of less than 5.0, the spreading amount of the potassium-based porous geopolymer soil acid conditioner is equal to or greater than 2-5 tons / hectare.
10. Use of the potassium-based porous geopolymer soil acidity improver according to claim 8 in engineering soil remediation, characterized in that: The engineering soil remediation includes roadbed reinforcement and slope stabilization. The remediation construction method includes the following steps: first, crushing and drying the original soil, then evenly spreading the potassium-based porous geopolymer soil acidity improver, and finally mixing and compacting the soil in layers according to the above steps. The operation is repeated three times, and the compacted thickness of each layer is not less than 10 cm. The film is then covered and maintained for 24 hours. 3 20% of the potassium-based porous geopolymer soil acid conditioner is added to the original soil.
Citation Information
Cited By
Nutrient soil preparation method based on geopolymer cooperating with titanium dioxide byproduct desulfurized gypsum, nutrient soil prepared by nutrient soil preparation method and application of nutrient soil
CN121312485A